Participatory teaching improves learning outcomes: Evidence from a field experiment in Tanzania - Martina Jakob; Konstantin Büchel; Daniel Steffen; Aymo Brunetti (University of Bern, Department of Economics, 2023)
Participatory teaching methods have been shown to be more successful than traditional rote learning in high-income countries. It is, however, less clear if they can help address the learning crisis in low- and middle-income countries, where classes tend to be large and teachers have fewer resources at their disposal. Based on a field experiment with 440 teachers from 220 schools in Tanzania, we use official standardized student examinations to assess the impact of a pedagogy-centered intervention. A five-day in-service teacher training on participatory and practice-based methods improved students' test scores 18 months later by 0.15σ. The additional provision of laptops with a learning software allowing teachers to refresh their content knowledge did not yield further learning gains for students. Complementary results from qualitative surveys and interviews suggest that the program was highly appreciated by different stakeholders, but that participants are unable to assess its impact along different dimensions, giving equally positive evaluations of its successful and its less successful elements.
Keywords: C93; I21; J24; O15; 330; productivity in education; participatory teaching; teacher content knowledge; computer-assisted learning; development economics